Tonsil volume, tonsil grade and obstructive sleep apnea: is there any meaningful correlation? (Clinics, 2011)
OBJECTIVES: The aims of this study were to evaluate the correlation between oropharyngeal examination and objective palatine tonsil volume in snoring adults and verify the influence of the oropharyngeal anatomy, body mass index, age, and severity of obstructive sleep apnea on actual tonsil volume. In addition, we aimed to assess the influence of tonsil size on obstructive sleep apnea in adults. INTRODUCTION: Pharyngeal wall geometry is often altered in adults who have obstructive sleep apnea, and this might influence the findings of the oropharyngeal examination that, in turn, are the key factors when considering surgical management for this condition. Furthermore, the correlation between the actual tonsil volume and the severity of obstructive sleep apnea in adults is currently unknown. METHODS: We prospectively studied 130 patients with obstructive sleep apnea or primary snoring who underwent pharyngeal surgery with intraoperative measurement of tonsil volume. We compared tonsil volume with preoperative polysomnography, oropharyngeal examination, and anthropometric data. RESULTS: We found a significant correlation between actual tonsil volume and subjective tonsil grade. We also found a significant correlation between tonsil volume and the apnea-hypopnea index. Using a multivariate linear regression model, tonsil volume was found to be significantly correlated with age, body mass index, and oropharyngeal examination, but not with polysomnography. Clinically, only the rare tonsil grade IV was indicative of more severe obstructive sleep apnea. CONCLUSIONS: There is a strong correlation between clinical tonsil grade and objective tonsil volume in snoring adults, and this correlation exists regardless of the presence or severity of obstructive sleep apnea. Pharyngeal tissue volume likely reflects the body mass index rather than obstructive sleep apnea severity.